Determinant of Indonesian Frozen Shrimp Export Volume to Japan - Maylan Iga Prastika; Joko Sutrisno; Ernoiz Antriyandarti (Faculty of Animal and Agricultural Science, Diponegoro University, 2026)
Shrimp is a leading export commodity in the fisheries sector in Indonesia, playing a significant role in generating foreign exchange earnings, particularly through exports to the United States and Japan. Despite its importance, the volume of Indonesian frozen shrimp exports to Japan has fluctuated in recent years. This research investigates the key factors influencing these export volumes, focusing on frozen shrimp production, international shrimp prices, the USD to IDR exchange rate, and Gross Domestic Product (GDP) of Japan). Data were sourced from UN COMTRADE, the World Bank, Statistics Indonesia (BPS), the Ministry of Marine Affairs and Fisheries, the Japan External Trade Organization (JETRO), and Trade Statistics of Japan. A quantitative research approach was employed, using multiple linear regression analysis to determine the relationships among the variables. The findings revealed that frozen shrimp production, the exchange rate, and GPD of Japan have a significant impact on export volumes, while international shrimp prices do not show a statistically significant effect. Among these, the GDP of Japan emerged as the most influential factor. Based on these results, policy recommendations include the enhancement of international branding, formulation of comprehensive production planning, and the improvement of product value and quality.